PENGATURAN KECEPATAN PUTARAN MOTOR DC BERBASIS KOMPUTER - Anshori, Yusuf (MEKTEK, 2009)
The development of industrial world needs an instrumentation automation that to support production process. For a true intelligent and flexible automated manufacturing system, the system should be able to respond to changing conditions by changing the manufacturing process all by itself. Computers can be programmed to